Cell junctions in the gut of Protura. - Xué, L; Romano, D (1992)
The main cell junctions in the intestinal tract of a small group of apterygotan insects, Protura, were examined in conventional thin sections, tracer-infiltrated sections and freeze-fracture replicas. The smooth septate junctions in the midgut of collembolan Tomocerus minor were also studied for comparison. Pleated septate junctions are found in foregut, hindgut and Malpighian papillae. They exhibit regular septa crossing the intercellular clefts in thin sections; and the septa with a pronounced zig-zag appearance run parallel to form a honeycomb structure in tracer-impregnated sections. After freeze-fracture undulating rows of intramembranous particles (IMPs) are visible on the P face. Smooth septate junctions are observed in the midgut. The intercellular septa often run in pairs for long tracts and exhibit a wavy course in lanthanum impregnated sections. The IMPs exhibited on the E face are usually separated one from another. Twin arrangement of particle rows is also apparent on the replicas. Gap junctions are frequent in both the midgut and hindgut and possess the conventional characteristics of 'inverted gap junction' with E face connexons. These results provide further evidence relating Protura closely to Collembola as well as to primitive arthropods.